A novel pro-inflammatory protein of Streptococcus suis 2 induces the Toll-like receptor 2-dependent expression of pro-inflammatory cytokines in RAW 264.7 macrophages via activation of ERK1/2 pathway - Zhang, Qiang; Yang, Yujie; Yan, Shuxian; Liu, Jiantao; Xu, Zhongmin; Yu, Junping; Song, Yajing; Zhang, Anding; Jin, Meilin (Frontiers in Microbiology, 2015)
Streptococcus suis 2 is an important swine pathogen and an emergent zoonotic pathogen. Excessive inflammation caused by S. suis is responsible for the high levels of early mortality observed in septic shock-like syndrome cases. However, the mechanisms through which S. suis 2 (SS2) causes excessive inflammation remain unclear. Thus, this study aimed to identify novel pro-inflammatory mediators that play important roles in the development of therapies against SS2 infection. In this study, the novel pro-inflammatory protein HP0459, which was encoded by the SSUSC84_0459 gene, was discovered. The stimulation of RAW 264.7 macrophages with recombinant HP0459 protein induced the expression of pro-inﬂammatory cytokines (IL-1β, MCP-1 and TNF-α). Compared with the wild-type strain, the isogenic knockout of HP0459 in SS2 led to reduced production of pro-inflammatory cytokines in RAW264.7 macrophages and in vivo. The pro-inflammatory activity of HP0459 was significantly reduced by an antibody against Toll-like receptor 2 (TLR2) in RAW264.7 macrophages and was lower in TLR2-deﬁcient (TLR2-/-) macrophages than in wild-type (WT) macrophages. Furthermore, specific inhibitors of the extracellular signal-regulated kinase 1/2 (ERK1/2) pathways signiﬁcantly decreased the HP0459-induced pro-inflammatory cytokine production, and a western blot assay showed that HP0459 stimulation induced the activation of the ERK1/2 pathway. Taken together, our data indicate that HP0459 is a novel pro-inflammatory mediator of SS2 and induces TLR2-dependent pro-inflammatory activity in RAW264.7 macrophages through the ERK1/2 pathway.